Reevaluation of the body mass estimate for the KNM‐ER 5428 Homo erectus talus. Issue 1 (3rd July 2019) - Cunningham, Deborah L.; Rogers, Melinda V.; Wescott, Daniel J.; McCarthy, Robert C.
Abstract: Objectives: In this study, we reexamined the body mass estimate for the Homo erectus specimen KNM‐ER 5428 based on talus dimensions. Previous estimates of >90 kg for this fossil are large in comparison to body mass estimates for other H. erectus specimens. Materials and methods: The study sample consisted of tali and femora of 132 modern cadaver males from a documented body mass skeletal collection. We recorded the talus trochlear mediolateral (TTML) breadth and femoral head diameter (FHD) for each modern human specimen, and obtained KNM‐ER 5428's TTML values from the literature. We developed regression formulae based on TTML using the body mass estimated from FHD for the entire human sample and for known body masses from a normal‐BMI subsample, and then used these formulae to calculate body mass for KNM‐ER 5428. In addition, we examined the range of body masses for individuals with TTML measurements comparable to KNM‐ER 5428. Results: The body masses of normal‐BMI individuals with a TTML ≥32.3 mm (the smaller of the two fossil measurements from the literature) ranged between 60.3 and 86.2 kg and averaged 72.3 kg. The body masses of normal‐BMI individuals with a TTML ≥33.7 mm (the larger measurement) ranged between 63.5 and 86.2 kg with a mean of 73.6 kg. The correlations between TTML and body mass are moderate. Revised body mass point estimates for KNM‐ER 5428 ranged between 69.2 and 81.6 kg based on TTML, and average 70.5 and 76.0 kg. Discussion: Results suggest previously published body mass estimates of KNM‐ER 5428's are too large. Its body mass was likely between 70 and 76 kg rather than >90 kg.